2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6631046
|View full text |Cite
|
Sign up to set email alerts
|

A lightweight soft exosuit for gait assistance

Abstract: Abstract-In this paper we present a soft lower-extremity robotic exosuit intended to augment normal muscle function in healthy individuals. Compared to previous exoskeletons, the device is ultra-lightweight, resulting in low mechanical impedance and inertia. The exosuit has custom McKibben style pneumatic actuators that can assist the hip, knee and ankle. The actuators attach to the exosuit through a network of soft, inextensible webbing triangulated to attachment points utilizing a novel approach we call the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
186
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(187 citation statements)
references
References 23 publications
0
186
0
1
Order By: Relevance
“…Nevertheless, advances in understanding and control of compliant actuators strongly support the development of artificial limbs and improve rehabilitation quality [32], [33]. They also pave the way towards support devices like lightweight powered exoskeletons [34], which could ensure the mobility for older people suffering from amyotrophia or support employees in heavy industries.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, advances in understanding and control of compliant actuators strongly support the development of artificial limbs and improve rehabilitation quality [32], [33]. They also pave the way towards support devices like lightweight powered exoskeletons [34], which could ensure the mobility for older people suffering from amyotrophia or support employees in heavy industries.…”
Section: Resultsmentioning
confidence: 99%
“…This approach based on skin strain analysis was first proposed in the work of Iberall (1964) and was continued by Newman et al (2005) to improve the mobility of astronauts. Today, this methodology is used in a variety of applications, including the design of a prosthetic socket (Lin et al, 2016), orthoses (Domingues et al, 2011), exoskeletons for gait assistance (Wehner et al, 2013) and functional clothes (Seo et al, 2013), among others.…”
Section: Introductionmentioning
confidence: 99%
“…While most research is focused on technical enhancements, a quantitative evaluation of the effectiveness is often missing (Dollar and Herr 2008). The metabolic energy expenditure, often calculated as metabolic power (W•kg -1 ) based on oxygen consumption and carbon dioxide using a standard equation (Brockway 1987) and body weight normalization, is a key value in the evaluation of several exoskeleton devices (Galle et al 2013a;Malcolm et al 2013;Mooney et al 2014;Norris et al 2007a;Sawicki and Ferris 2008, 2009a, 2009bWehner et al 2013). Regardless of the functional goal of the device, reducing the metabolic power will improve the usability of the exoskeleton (Ferris et al 2007) and can therefore be considered a prime outcome when evaluating exoskeleton effectiveness, that can even be used to drive kinematic behavior with exoskeletons (Collins and Jackson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Mooney et al (2014) showed that it is possible to make a fully autonomous exoskeleton that assists plantarflexion and that can reduce the metabolic power of loaded walking with 8% versus normal walking if the design of the device is altered in order to reduce distal mass. Furthermore, there is increasing progress in energy recycling approaches (Collins and Kuo 2010;Donelan et al 2008;Li et al 2009;Malcolm et al 2013, Unal et al 2012) and soft exosuits (Wehner 2013), which makes it likely that autonomous ankle-foot exoskeletons can become a permanent fixture in daily life.…”
Section: Introductionmentioning
confidence: 99%